2018
DOI: 10.1016/j.nmd.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel valosin-containing protein mutations associated with multisystem proteinopathy

Abstract: Over fifty missense mutations in the gene coding for valosin-containing protein (VCP) are associated with a unique autosomal dominant adult-onset progressive disease associated with combinations of proximo-distal inclusion body myopathy (IBM), Paget's disease of bone (PDB), frontotemporal dementia (FTD), and amyotrophic lateral sclerosis (ALS). We report the clinical, histological, and molecular findings in four new patients/families carrying novel VCP mutations: c.474 G > A (p.M158I); c.478 G > C (p.A160P); c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…In the original report, six different disease-causing mutations in VCP were identified. However, at the time of writing, 45 different pathogenic VCP mutations have now been identified in patients with MSP (Table 4) [58]. Whilst mutations have been identified throughout the gene, the majority are situated in exons 3-5 which encode the N-terminal domain which is involved in ubiquitin binding and binding of co-factors essential for VCP's function.…”
Section: Geneticsmentioning
confidence: 99%
“…In the original report, six different disease-causing mutations in VCP were identified. However, at the time of writing, 45 different pathogenic VCP mutations have now been identified in patients with MSP (Table 4) [58]. Whilst mutations have been identified throughout the gene, the majority are situated in exons 3-5 which encode the N-terminal domain which is involved in ubiquitin binding and binding of co-factors essential for VCP's function.…”
Section: Geneticsmentioning
confidence: 99%
“…Many studied reported that more than 50 missense mutations in gene coding VCP is causative in many neurodegenerative diseases characterised by ALS, FTD, IBM, CMT2Y, and PBD ( Al-Tahan et al, 2018 ). Approximately 9% of patients with VCP mutations had ALS phenotype, 4% with Parkinson's disease, and 2% has been diagnosed with Alzheimer's ( Al-Obeidi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a literature review on the clinical and genetic characteristics of previously reported ALS‐VCP cases (Table S1), 2,4–7,16,23–33 and illustrated mutation sites in VCP associated with ALS, IBMPFD, and other phenotypes (Figure S1). 2–5,7,16,20–86 A total of 59 cases have been reported, with the disease typically developing in patients in their 40s–50s, and 14 of the 33 cases survived without artificial respiration for more than five years. Given that the epidemiological studies of general ALS suggest that the peak prevalence is observed in patients in their 70s–80s, and that the median survival time is two to four years, 87–91 the ALS‐VCP cases might be characterized by relatively early disease onset and slow disease progression.…”
Section: Discussionmentioning
confidence: 99%